Rhodium‐Catalyzed Enantioselective Intramolecular CH Silylation for the Syntheses of Planar‐Chiral Metallocene Siloles1. Issue 23 (23rd April 2015) - Zhang, Qing‐Wei; An, Kun; Liu, Li‐Chuan; Yue, Yuan; He, Wei
Abstract: Reported herein is the rhodium‐catalyzed enantioselective CH bond silylation of the cyclopentadiene rings in Fe and Ru metallocenes. Thus, in the presence of ( S )‐TMS‐Segphos, the reactions took place under very mild conditions to afford metallocene‐fused siloles in good to excellent yields and with ee  values of up to 97 %. During this study it was observed that the steric hindrance of chiral ligands had a profound influence on the reactivity and enantioselectivity of the reaction, and might hold the key to accomplishing conventionally challenging asymmetric CH silylations. Abstract : New on the (metallo)cene : The title reaction of cyclopentadiene (Cp) rings in Fe and Ru metallocenes is reported. Fine‐tuning the steric hindrance of diphosphine ligands led to the identification of ( S )‐TMS‐Segphos [( S )‐L ], which enabled efficient, enantioselective CH silylation of the Cp rings in metallocenes under mild reaction conditions. cod=1, 5‐cyclooctadiene, TMS=trimethylsilyl.